Call me Aram - Skrypuch, Marsha Forchuk; Wood, Muriel (Markham, Ont. : Fitzhenry & Whiteside, 2009)
"Aram Davidian is one of a group of Armenian refugee orphans who made long journey from Corfu, Greece, to a farm in Georgetown, Ontario. And like others, Aram is delighted with the beauty of his new home and the kindness of the people who have sponsored them. But something isn't quite right. Why do his Canadian hosts keep calling him David Adams?" --Back cover.
Sequel to: Aram's choice.
Includes historical note.
JF/CDN ak
Keywords: Armenian massacres, 1915-1923 -- Turkey -- Juvenile fiction; Armenian massacres survivors -- Ontario -- Juvenile fiction; Orphans -- Juvenile fiction; Refugees -- Canada -- Juvenile fiction; Names, Personal -- Juvenile fiction; Identity -- Juvenile fiction; Refugees -- Cutural assimilation -- Canada -- Juvenile fiction; Canadian fiction, Juvenile; Historical fiction, Juvenile